The personalized context‐aware mobile advertisement system using a novel approaching detection method over cellular networks. (10th June 2013) - Huang, Chung‐Ming; Lin, Shih‐Yang; Hsieh, Tsung‐Han
SUMMARY With the rapid development of smartphones and personal tablet computers, it brings a greatly growing rate of ubiquitous applications for location‐based services (LBS). One famous LBS is the mobile advertisement. A mobile advertisement system brings benefits and opportunities among users, service providers, and advertisers. In this paper, we propose a personalized context‐aware mobile advertisement system (PCA‐MAS) over cellular networks, which contains two new techniques called (i) approaching detection method (ADM) and (ii) context‐aware ad targeting method (CAADTM). ADM can find some point of interests that a user is approaching; CAADTM pushes advertisements that satisfy user's requirement based on the user's context, that is, user's profile, current time, current position, and so on. Our experimental results show that (i) ADM has the good hit rate to determine those point of interests that a user is approaching within the 150‐m radius of the approaching range, and (ii) CAADTM has the good hit rate of finding appropriate advertisements that a user prefers through the favorite content table filtering, the annoying content table filtering, and the advertisement clicking feedback. Copyright © 2013 John Wiley & Sons, Ltd.